Adunqiaolu: new evidence for the Andronovo in Xinjiang, China. (5th June 2017) - Jia, Peter W.; Betts, Alison; Cong, Dexin; Jia, Xiaobing; Dupuy, Paula Doumani
Abstract: Abstract : Bronze Age social and cultural interconnections across the Eurasian steppe are the subject of much current debate. A particularly significant place is occupied by the Andronovo Culture or family of cultures. Important new data document the most easterly extension of Eurasian Bronze Age sites of Andronovo affinity into western China. Findings from the site of Adunqiaolu in Xinjiang and a new series of radiocarbon dates challenge existing models of eastward cultural dispersion, and demonstrate the need to reconsider the older chronologies and migration theories. The site is well preserved and offers robust potential for deeper study of the Andronovo culture complex, particularly in the eastern mountain regions.